Real-time Responses System Dalam Peningkatan Pelayanan Rumah Sakit Arun Lhokseumawe Menggunakan Metode Natural Language Processing: Studi Kasus pada Rumah Sakit Arun untuk Meningkatkan Kecepatan Pelayanan - Silfa Maharani Br Padang; Muhammad Fikry; Zahratul Fitri (Universitas Muhammadiyah Riau, 2024)
Abstract Based on information from the Central Statistics Agency, the population of of Lhokseumawe City reached 191,396 people in 2022, which requires Rumah Sakit Arun Lhokseumawe to enhance its healthcare services to the community. The increase in population presents challenges for the hospital in addressing patients with health issues. Therefore, the author proposes the development of a